A career development scale for high school students - Cauyan, Jacklyn Marie L. (College of Education, University of the Philippines Diliman, 2019)
The purpose of this study was to develop a career assessment scale that would determine the factors that affect students' career choice. The psychometric properties of the scale and its usability in terms of addressing the need for a more comprehensive approach to career guidance were established. The instrument which was locally made is anchored on culturally-relevant framework to assess students in their career awareness and decision-making. Using the explanatory sequential design, the study involved both qualitative and quantitative methods. The first phase of the study involved determining the factors that affect career choices of the students through focus group discussions and literature review. Data gathered from this phase became the basis of the initial item pool consisting of 117 items which was given to panel of experts for content validation and pilot-testing with students. The second phase involved the administration of the preliminary scale with 87 items to 1393 high school students and the evaluations of its psychometric properties. Principal component analysis with orthogonal rotations was conducted to determine the underlying factor structure and grouped the items into 8 subscales: career learning opportunities, multimedia exposure, school influence, family influence, knowledge, skills, and attitudes, labor market demands, values, financial security. The final scale has 66 items with over-all-reliability of .932 while all subscales had sufficient reliability (alpha >=.70). Counselors who utilized the scale among their clients revealed that it helped their clients in their career awareness and career exploration. The scale can also be used in program development, career guidance activities, and as a springboard in counseling sessions. Implication and recommendations are discussed.